Juvenile laryngeal papillomatosis in Benin : Epidemiological, Diagnostic, therapeutic and evolutionary aspects......... - LAWSON ÉPSE AFOUDA, SONIA RUTH JOSÉPHINE; HOUNKPATIN, Spéro; AVAKOUDJO, FRANÇOIS; BRUN, LUC; ADJIBABI, WASSI (My University, 2015)
..................
Keywords: Juvenile laryngeal papillomatosis . Epidemiology; diagnosis; Treatment; complications